A közösségi energiatermelés szerepe a jövő energiarendszereiben - Horváth , Péter János (Kultúratudományi Szemle, 2022)
The role of community energy production in future energy systems Péter János Horváth Growing environmental concerns and the spread of renewable energy also spurred the so called decentralization process of predominantly centralized energy systems. Consumers and communities are key drivers of this process, not only as energy consumers, but also by producing and storing clean energy, aggregating individual energy productions, and even as distributors or energy service providers. The new EU legislation also recognizes the important role of energy communities in the energy transformation process, which can bring about better social acceptance of renewable energy production, but also many environmental, economic or social benefits to the local community. Our study aims to present the nature and role of community energy production in energy systems, and outlines a vision of community energy for Hungary and the EU as a whole.